Improving Procedure Text Writing Skills Through Make A Match Learning Model in Junior High School - Oktaviana Zulfa, Adelia; Senowarsito, Senowarsito (Pascasarjana Universitas PGRI Semarang, 2023)
This Classroom Action Research aims to improve students' ability in writing procedure texts through Make a Match learning model. The subjects in this study were 33 students of class VII A SMP Negeri 36 Semarang. Data were collected in one cycle through tests, classroom observation, and documentation. The tests were conducted in the form of pre-test, post-test of cycle I, and post-test of cycle II. The instruments used were test sheets, observation guidelines, and documentation guidelines. Data were analyzed using qualitative descriptive method. The results showed that students took an active role in their learning activities. The quality of their writing also improved. Their average score increased from 67 (Pre-test), 76 (Cycle I), and 82 (Cycle II). In conclusion, the use of Make a Match learning model is effective to improve students' ability in writing procedure text. The researcher hopes that the use of Make a Match learning model can be used by English teachers in teaching English, especially in teaching writing procedure text.